Evaluation of carboxylic acids as sustainable compatibilizing agents on blend sheets properties based on thermoplastic babassu starch and polypropylene - Maniglia, Bianca Chieregato; Vedove, Thaís Maria Aimola Ronca Dale; Tadini, Carmen Cecília (Frontiers in Food Science and Technology, 2022)
Polypropylene/babassu thermoplastic starch (PP/TPS, 70:30 w/w) blend sheets were prepared as an alternative material to use in disposable packaging, reducing the negative environmental impact of synthetic polymer. Three different carboxyl acids: palmitic (PP/TPS/P), citric (PP/TPS/C), and stearic (PP/TPS/S), were used as natural compatibilizing agents (NCA) and compared to the conventional synthetic maleic anhydride (PP/TPS/M), concerning mechanical, physical, crystallinity, and morphological properties of the blend sheets. The blend sheets without or with compatibilizing agents resulted in dark coloration, higher opacity, higher thickness, lower resistance to break, flexibility and rigidity, higher moisture, solubility in water, hydrophilicity, lower crystallinity, and more heterogeneous morphology in comparison to PP sheets. The presence of compatibilizing agents was observed to improve the mechanical and physical properties of the blend sheets, resulting in materials stronger and less hydrophilic. The citric acid was able to act similarly to the synthetic maleic anhydride, resulting in blend sheets with similar mechanical and physical properties. Finally, this work shows that the natural compatibilizing agent citric acid was analogous to the commercial one, synthetic maleic anhydride, bringing a more sustainable alternative. In addition, this work allowed assessing a new source of starch and offering one more alternative for applying this source to the plastic packaging sector.